Perenialitas Kritis Sebagai Bentuk Evaluasi Atas Implementasi Spiritualitas Tentang Filsafat Nusantara: Critical Perennialism as a Form of Evaluation of the Implementation of Spirituality Regarding Nusantara Philosophy - Kuswanjono, Arqom; Sahadewa, Ngurah Weda; Sukri, Ridwan Ahmad (Jurnal Filsafat Indonesia, 2024)
The basic problem of this research is to explore perennial thought in the spirituality. Nusantara Philosophy as a big problem in the context of how to develop it. This research is an initiative to get the core of the thought must be evaluated. The Nusantara philosophy has a unique in order to solve the problem. Problem in the meaning of the Nusantara philosophy has a special purpose. The special purpose of Nusantara philosophy to solve the problem of life. The problem of life dilemma. Method of this research is critical constructive which is bring the Nusantara philosophy to the spirituality values. Firstly, the position of spirituality has to be flexible. It is a big problem for spirituality because flexibility it does not mean nothing. Secondly, flexibility is not becoming isolate of the truth in nature. Thirdly, to make an effort in order to construct the critical spirituality. Results of the research show about Nusantara Philosophy can be developed based on the spirituality which is understood to build the construction of reality of the nation culture. It is a big problem in the context of the Nusantara Philosophy because of the reality of scientific can be developed by a lot of methods. For that, it is important to know about how the spirituality can be a basic need in order to understand about the Nusantara Philosophy. It is important to understand based on culture. Therefore, firstly, critical perennial can create an important notion to the culture and secondly to give an opportunity in order to make a decision in the context of Nusantara philosophy.